Acetabularia caliculus (J.V.Lamouroux, Quoi & Gaimard, 1824), in the Gulf of Antalya: A second discovery - Ãœstüner, Hatice; Gökoğlu, Mehmet (Universitas Malikussaleh, 2024)
During scuba-diving activities on October 26, 2021, at Konyaalti Beach (36o 52' 58'' N 30o 41' 06'' E) of the Gulf of Antalya, another Acetabularia species was discovered after the vegetation of Acetabularia acetabulum. According to the species guide, this algae species was identified as Acetabularia caliculus (JVLamour, Quoy & Gaimard, 1824). This species was first reported in the Gulf of Antalya in 2018. This study presents a second discovery of the species in the Gulf of Antalya.Keywords: Acetabularia caliculus; Gulf of Antalya; Second Report